The Role of Verbal and Nonverbal Communication in a Two-Person, Cooperative Manipulation Task. (7th August 2014) - Parikh, Sarangi P.; Esposito, Joel M.; Searock, Jeremy
Abstract : Motivated by the differences between human and robot teams, we investigated the role of verbal communication between human teammates as they work together to move a large object to a series of target locations. Only one member of the group was told the target sequence by the experimenters, while the second teammate had no target knowledge. The two experimental conditions we compared were haptic-verbal (teammates are allowed to talk) and haptic only (no talking allowed). The team's trajectory was recorded and evaluated. In addition, participants completed a NASA TLX-style postexperimental survey which gauges workload along 6 different dimensions. In our initial experiment we found no significant difference in performance when verbal communication was added. In a follow-up experiment, using a different manipulation task, we did find that the addition of verbal communication significantly improved performance and reduced the perceived workload. In both experiments, for the haptic-only condition, we found that a remarkable number of groups independently improvised common haptic communication protocols (CHIPs). We speculate that such protocols can be substituted for verbal communication and that the performance difference between verbal and nonverbal communication may be related to how easy it is to distinguish the CHIPs from motions required for task completion.